Boundedness and Compactness of Hankel Operators on Large Fock Space. (12th January 2022) - Wang, Xiaofeng; Zeng, Zhicheng
Abstract : We introduce the BMO spaces and use them to characterize complex-valued functions f such that the big Hankel operators H f and H f ¯ are both bounded or compact from a weighted large Fock space F p ϕ into a weighted Lebesgue space L p ϕ when 1 ≤ p < ∞ .